A developmental ecological study of novel metaphoric language use. (January 2016) - Read, Catherine; Szokolszky, Agnes
Abstract: From the perspective of the ecological direct realist approach to perceiving-acting-knowing, we argue that linguistic metaphor involves understanding one kind of thing by means of a different kind of thing. This understanding is based on invariants in an ambient stimulus array that specify objects and events over time, and, therefore, the metaphoric process is rooted in perception. The present research investigated children's and adults' knowledge of ordinary kinds of objects and events, the development of their ability to detect metaphoric resemblances across these real kinds, and their abilities to respond to discourse contexts that supported metaphor use. We used pairs of photographs depicting objects and events from verbal metaphors earlier produced by other children. Thirty participants at each age group (4, 6, 8, 10, adults) first said what they knew of each depicted object or event. Then half of the participants in each age group chose depictions from the whole set of photographs that were "like" the given standards; the other half chose those that were "of the same kind". Finally, the experimenter encouraged metaphor use by showing pictures from metaphoric pairs to all the participants and asking questions about the pictures. Participants at all ages described the objects and events predominantly in terms of functions, physical properties, and dynamic properties. Whereas metaphoric matches in the "kind" condition were rare at all ages, they were frequent in the "like" condition, and increased with age. Metaphor use also increased with age and participants did not use metaphors about objects or events that they had said were of the same kind. Thus, children know that metaphors are about different real kind things and, therefore, their utterances are truly metaphoric. Even though these abilities begin at early ages, they continue to develop in facility and frequency at least to adulthood. Future studies will investigate developments in the forms of metaphoric utterances, and in the links between visual and verbal metaphors. Highlights: We investigated children's ability to detect metaphoric resemblances depicted in photographs. Even young children are able to resonate to metaphoric resemblances in the world. Perceptual information specifying objects and events is critical in metaphor use.